2013
DOI: 10.2478/msr-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

A New Neutrosophic Approach of Wiener Filtering for MRI Denoising

Abstract: In this paper, a new filtering method based on neutrosophic set (NS) approach of wiener filter is presented to remove Rician noise from magnetic resonance image. A neutrosophic set, a part of neutrosophy theory, studies the origin, nature and scope of neutralities, as well as their interactions with different ideational spectra. Now, we apply the neutrosophic set into image domain and define some concepts and operators for image denoising. The image is transformed into NS domain, described using three membersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Every event in the neutrosophy set (NS) has a certain degree of truth (T), indeterminacy (I), and falsity (F), which are independent from each other. Previously reported studies have demonstrated the role of NS in image processing [26,27].…”
Section: Neutrosophic Imagesmentioning
confidence: 99%
“…Every event in the neutrosophy set (NS) has a certain degree of truth (T), indeterminacy (I), and falsity (F), which are independent from each other. Previously reported studies have demonstrated the role of NS in image processing [26,27].…”
Section: Neutrosophic Imagesmentioning
confidence: 99%
“…In this paper, a new hybrid algorithm for binarization of degraded Arabic manuscript image is proposed. It combines the famous adaptive algorithm of Sauvola's (8) and a NS binarization algorithm of [9] into a hybrid one. Neutrosophic set (NS) approach is quite new and have been useful for various image processing tasks such as segmentation, thresholding, and denoising [7].…”
Section: Introductionmentioning
confidence: 99%
“…Memberships are calculated based on the relative distance (Euclidean distance) of the object o j to the centroids using Equation (5). After the memberships of all objects have been found, the centroids of the clusters are calculated using Equation (4). The process stops when the centroids from the previous iteration are identical to those generated in the current iteration [6].…”
Section: Fuzzy C-means Clustering (Fcm)mentioning
confidence: 99%
“…(any color except white and black). According to this theory every idea <A> tends to be neutralized and balanced by <Anti-A> and <Non-A> ideas [4].…”
Section: Introductionmentioning
confidence: 99%